Exercise-associated Muscle Cramps in Runners: A Review - Ali Fattahi; Mahboobeh Dehnavi; Leila Hamzeh (Biyumikānīk-i varzishī)
Objective: Exercise-associated Muscle Cramp (EAMC) is an intense, painful, and involuntary contraction of skeletal muscles during a physical activity. Runners are more prone to this syndrome than other athletes. The present paper aims to review of the literature on EAMC in runners to determine the reasons and nature of EAMC in this sports field. Methods: A search was conducted for related studies from 1997 to 2021 in MEDLINE/PubMed, EMBASE/SCOPUS, LILACS, CINAHL, CENTRAL, Web of Science, PEDro, Google Scholar as well as MagIran, IranDoc, IranMedex, MedLib using MeSH Keywords. The reference section of the studies were also checked to find more studies. Finally, 15 eligible papers on EAMC in runners were reviewed and findings were reported. Results: Several factors were found to be effective in EAMC among runners, including dehydration, electrolyte deficit, cold, long training or competition period, increased body temperature during training or competition, history of injury or muscle cramp, increased training intensity in short time, and dietary restrictions. Conclusion: The cause of EAMC in runners seems to be multifactorial.